Frontispiece: Inverted Fuel Cell: Room‐Temperature Hydrogen Separation from an Exhaust Gas by Using a Commercial Short‐Circuited PEM Fuel Cell without Applying any Electrical Voltage. Issue 27 (26th June 2015) - Friebe, Sebastian; Geppert, Benjamin; Caro, Jürgen
<x xml:space="preserve">Abstract</x> Hydrogen Separation A short‐circuited fuel cell with a Nafion membrane is used by J. Caro et al. in their Communication on page 7790 ff., to separate hydrogen from exhaust gases.